Internal control quality and voluntary disclosure: does CEO duality matter?. Issue 2 (31st December 2020) - Khlif, Hichem; Samaha, Khaled; Amara, Ines
Abstract : Purpose: The authors examine the association between internal control quality (ICQ) and voluntary disclosure and test whether chief executive officer (CEO) duality, as a proxy for CEO structural power, moderates such a relationship in an emerging market (Egypt). Design/methodology/approach: ICQ is measured using a survey of external auditors, while a content analysis approach is used to measure the level of voluntary disclosure in annual reports. Findings: Based on a sample of 512 firm-year observations over the period of 2007–2014, the authors document that ICQ is positively and significantly associated with voluntary disclosure, suggesting that better controls improve corporate reporting policy. In addition, CEO duality moderates the association between ICQ and voluntary disclosure since this positive relationship association becomes insignificant for companies characterised by CEO duality. These results remain stable after controlling for endogeneity (self-selection problem), political instability and industry characteristics. Research limitations/implications: The findings of the study provide preliminary evidence on the association between ICQ and voluntary disclosure, and how CEO structural power may affect this association. Future empirical investigations may extend this work to cover the relationship between ICQ and other attributes of corporate transparency including earnings quality and accounting conservatism. Practical implications: The findings highlight the need for Egyptian regulators to enact new rules obliging firms to communicate information about ICQ or charging auditors to report information about firm's ICQ in their reports. The results also alert policymakers about the adverse effect of combined leadership structure (CEO duality) since it mitigates the positive impact of ICQ on voluntary disclosure. Originality/value: The authors contribute to internal control literature by exploring the association between ICQ and voluntary disclosure on an emergent unregulated market with respect to internal control disclosure. They also highlight how CEO duality, as a proxy for CEO power, mitigates the beneficial effect of ICQ on corporate reporting policy on the Egyptian stock exchange (EGX).